Names of buttocks in the Northern Samogitian subdialect - Pakalniškienė, Dalia; Lubienė, Jūratė (Baltistica, 2023)
This article presents a study of the Northern Samogitian lexical thematic group of names of buttocks and their parts. The aim of this research is to determine which lexemes are used in the subdialect to refer to buttocks and their parts, as well as to explore the linguogeographical, nominational, and motivational characteristics of these names.
Keywords: Northern Samogitian subdialect; onomasiology; semasiology; somatonyms; names of buttocks and their parts